PUBLIC POLICY AND SPECIAL AUTONOMY IN PAPUA AND WEST PAPUA - Suharno, Suharno (Universitas Negeri Yogyakarta, 2021)
Serious efforts to decentralize Indonesia have only been carried out since the reformation period began in the midst of the crisis that hit Asia and coincided with the process of changing leadership in Indonesia from Suharto to Habibie. Regional autonomy is considered to be able to answer the demands of equitable distribution of socio-economic development, governance, and the development of an effective political life because it is believed to be able to guarantee the handling of community demands in a varied and fast manner. Article 18B of the 1945 Constitution of the Republic of Indonesia recognizes and respects special or special regional government units which are regulated by law. The special autonomy implemented in Indonesia can be categorized as asymmetric decentralization, including Papua and West Papua. Politically, the issue of Papua Autonomy has gained light and legitimacy as well as a normative basis with the issuance of the Special Autonomy Law, but in reality the implementing regulations are not perfect. A grounded public policy is needed that takes into account the aspirations of the people of Papua and West Papua with the Special Autonomy Law as a normative basis because the actual role of the Special Autonomy Law in the welfare of the people of Papua and West Papua is as legalization to manage Papua and West Papua in particular by taking into account the various characteristics that they have. towards progress and prosperity.